Formulasi Pakan Lengkap (Complete Feed) Berbasis Limbah Pertanian Sebagai Pakan Ternak Kambing Di Kecamatan Kromengan Kabupaten Malang - Dyah Lestari Yulianti; Permata Ika Hidayati; Ahmad Shodiq (Jurnal Pemberdayaan Masyarakat, 2018)
Farmers in Kromengan Village, Kromengan District, Malang Regency have problems providing forage feed for their goats. Appropriate technology offered on this community services program is the silage technology on agricultural by-product. A target of this community services programes is a group of goat farmers "Sinar Harapan" with the number of farmers 15 people who have of 3-4 goats respectively. The feed ingredients used to make silage are rice straw, sugar cane, pollard, urea, starbio, EM4, and water. Complete feed composed include silage 51.57% and leguminous 48.43%. The results of community services program activities increased: (1) the understanding of target group about complete feed formulation based on agricultural by-product as goat feed about 90%; (2) goat body weight gain 150 g / head/day; and (3) farmer income of Rp 432,109 ,-/month. It is suggested to implement community services program by utilizing silage technology which based local agricultural by-product based as roughage source for ruminants.